Potensi Ekstrak Etanol Buah Belimbing Wuluh (Averrhoa bilimbi L.) sebagai Alternatif Sediaan Diuretik Alami - ANDRIYANTO ANDRIYANTO; NASTITI KUSUMORINI; FITRIA YUSKHA (Fakultas Farmasi Universitas Pancasila, 2011)
Diuretics use as first treatment in hypertension and heart failure. Empirically, community use belimbi as diuretic. Preliminary study to explore the potency of bilimbi ethanolic extract as a natural diuretic was conducted using ninety male mice which divided into 6 groups. Each group consist of three sub-group of 5 mice respectively for three replications. Group 1 was given orally saline solution of tween 80, Group 2 was given orally urea solution 500 mg/kg BW, Group 3 was given orally furosemide 3 mg/kg BW, Group 4 was given orally extract of bilimbi 2.5 g/kg BW, Group 5 was given orally extract of bilimbi 5 g/kg BW, and Group 6 was given orally aquadest. The diuretic activity was determined by measuring cumulative urine volume every 1 hour during 5 hours post administration. The result showed that 2.5 g/kg BW had a strong diuretics activity 2 hours post administration and reached its maximum activity 3 hours post administration. At the peak of diuretic activity, extract of bilimbi 2.5 g/kg BW increased diuretic effect by 219% as compared to the aquadest and 41,5% as compared to the furosemide. It is concluded that extract of bilimbi has a potency as a natural diuretic.